Perilaku Harian Ikan Timpakul (Periophthalmodon schlosseri) di Lingkungan Pasang Surut Desa Tanipah, Muara Sungai Barito, Kalimantan Selatan - Gina Seisaria; Muhamat Muhamat; Heri Budi Santoso (Universitas Lambung Mangkurat, 2017)
Mangrove forests, which are tidal areas, are decreasing in size due to land conversion, causing P. schlosseri habitat to shrink. Daily behavior is important to know as initial information in conservation efforts. Observation of daily behavior was carried out using the scan sampling method. The observed behavior is moving behavior, including walking and swimming activities. Swimming is done with the head position above the water so that their eyes are not submerged in the water. P. schlosseri is outside the nest when high tide occurs. P. schlosseri interacted with each other at the edge of the nest and at the mouth of the nest in the morning and afternoon. P. schlosseri preys on crabs which are usually on the banks of the river at low tide in the morning.